Against The Stereotype Of Being The Second-Class Of The Society In Alexandra Ripley's Scarlett Novel (1991):A Feminist Approach - Priyanto, Sulis (2012)
The research is proposed to analyze against the stereotype of being the second class of the society in Alexandra Ripley's Scarlett by a Feminist Approach. The research sets two objectives: the first is to analyze the novel in term of structural elements, and the second is to analyze the novel based on the Feminist Perspective. This study is a qualitative study using the novel of Alexandra Ripley's Scarlett as the object analysis of the study. There are two kinds of data sources: primary and secondary. The primary data sources is the text of the novel Alexandra Ripley's Scarlett and the secondary data sources are some books and article related to the subject. The method of collecting data in the research is library research by summarizing, paraphrasing, and documenting the data. In analyzing the data, the writer employs descriptive analysis. The outcome of the study is as follows: first, in this novel, Alexandra Ripley wants to illustrate how women are subordinate in patriarchal society. Second, in this novel, Alexandra Ripley wants to say that women need to against the stereotype of being the second-class of the society being to get independence in their life and that women's independence is not given but must be struggled for. The last, in this novel Alexandra Ripley wants to assert that in order to get their independence; women should rebel against patriarchal society in the issue of women's independence, position, role, and participation.